Management of Pain During Propofol Injection Using Intravenous Nitroglycerine - Hossain, Muhammad Sazzad; Rashid, Mohammad Mamunur; Babu, Md Anisur Rahman; Sultana, Afsana; Mahfuz, Md Sirajul Islam; Rahman, Abdur; Mandal, Muhammad Alamgir (KYAMC Journal, 2020)
Background: Propofol is an intravenous (IV) anesthetic agent, can irritate the skin, mucous membrane and venous intima. The main drawback is the pain at injection site following its intravenous injection. Objectives: This study was performed to evaluate the effect of intravenous nitroglycerine on pain in patients following propofol injection. Materials and Methods: Eighty adult patients of both sexes, aged 20-50 years, according to American Society of Anesthesiologists (ASA) physical status were divided into two equal groups (n=40) to receive 200 mcg intravenous nitroglycerine diluted in 10 ml saline (group A) and 10 ml normal saline as placebo (group B) at an ambient operating room temperature in a randomized and double blinded fashion to compare the pain-relieving effects of the drugs during propofol injection before the patients lost consciousness. The pain on propofol injection was assessed according to the Mc Crirrick and Hunter scale. Results: The overall incidence and severity of pain were significantly less in Groups A (nitroglycerine group) than group B (placebo group) (p< 0.05). The incidence of mild and moderate pain in Group A versus group B was 25% vs 45% and 15% vs 30% respectively (p<0.05). The incidence of score '0' (no pain) was higher in Group A (60%) than Group B (25%) (p<0.05). Conclusion: Pretreatment with 200 mcg nitroglycerine with venous occlusion for one minute is effective pretreatment in alleviating propofol injection pain when compared to placebo. KYAMC Journal Vol. 10, No.-4, January 2020, Page 202-205